Persistence and change of the peasantry. A critical approach to "La morada de la vida" from contemporary Marxism - Diez, Carolina; Kostlin, Laura (Centro de Historia Argentina y Americana, 2009)
This work aims to identify and contrast the theoretical and methodological strategies used by Beatrice M. Alasia de Heredia and Bronislaw Galeski, to study the economic unit of rural production. We take as reference two works of authors that we consider most relevant for studies of peasantry: "La morada de la vida. Trabajo familiar de pequeños productores del nordeste de Brasil" (2003) y "Sociología del campesinado" (1977) respectively. While both works belong to different disciplinary traditions, analyzing the economic unit of rural production they consider its persistence in the capitalist economic system.